EFEK BULLYING TERHADAP PROSES BELAJAR SISWA - M. Agus Samsudi; Abdul Muhid (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2020)
Abstract: The school is a place for students to achieve their learning goals. Effective learning requires comfort for students. With the convenience of the participants encourage students to achieve learning success. Bullying is an act of violence and causes discomfort to the victims. Bullying is not in accordance with the meaning of the purpose of education. Bullying can occur anywhere. Most perpetrators of bullying are friends and do not rule out the perpetrators of bullying are educators, family relatives and the surrounding environment. Forms of bullying vary, from verbal to cyber bullying. The research method uses library research. The population is taken from a collection of journals to make conclusions. From the sample of victims of bullying, they experience dizziness, shame, depression, no schooling, hand injuries, forehead injuries and some even want to commit suicide. IRCW data, KPAI data show that the number of victims of bullying has increased every year. From the research references which are the source of literature, it shows that the results of research every year of bullying have increased, Educational institutions are inseparable from bullying. The need for a handling mechanism so that the environment of Educational institutions is free from bullying.